Discovering the impact of value evolution in marketing communication strategies for Czech consumers. Artistray cosmetics. - Sedláková, Tereza; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The thesis covers the topic of the transition from a non-vegan brand to a vegan brand applied to the Artistry case. All findings are based on the determination of brand equity dimensions. The thesis also explains multilevel marketing communication because the research brand is manufactured by Amway, which uses this type of marketing. Based on brand equity, this thesis aims to determine critical factors that will assess the implementation of marketing communication strategy for vegan brands for Czech customers. The thesis reveals that the essential dimensions for the Czech customer in vegan cosmetics are: Perceived Quality, Brand Association, Brand Loyalty and Brand Awareness of vegan cosmetics. Perceived Quality and Brand association are two dimensions which influence Czech customers’ decision-making. The thesis shows the insights into customer motivation to buy vegan cosmetics, such as environmentally friendly philosophy, non-testing on animals, or design. The practical part of the thesis is based on a quantitative questionnaire and shows Czech customers’ needs for vegan cosmetics. Finally, the findings are applied to the Artistry case, and an improved communication strategy is proposed.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses